2023
DOI: 10.1007/s10072-022-06583-x
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy in subcortical gray matter in adult patients with moyamoya disease

Abstract: Background Acute cerebrovascular accidents, long-term hypoperfusion, and/or remote neuronal degeneration may lead to structural alterations in patients with moyamoya disease (MMD). This study sought to comprehensively investigate the distribution characteristics of subcortical gray matter volume and their correlations with angiographic changes in the intracranial artery in patients with MMD. Method One hundred forty-two patients with MMD and 142 age- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On MRI, patients often have sequelae of previous ischemic changes similar to the patient in this case. Structural alteration patterns of subcortical gray matter and atrophy of the hippocampus and amygdala can also be seen in moyamoya and may suggest cognitive or affective impairment [12]. The patient in this case exhibited characteristics of antisocial personality disorder potentially caused or exacerbated by underlying moyamoya disease.…”
Section: Discussionmentioning
confidence: 68%
“…On MRI, patients often have sequelae of previous ischemic changes similar to the patient in this case. Structural alteration patterns of subcortical gray matter and atrophy of the hippocampus and amygdala can also be seen in moyamoya and may suggest cognitive or affective impairment [12]. The patient in this case exhibited characteristics of antisocial personality disorder potentially caused or exacerbated by underlying moyamoya disease.…”
Section: Discussionmentioning
confidence: 68%
“…For example, MMD patients showed decreased gray matter volume and damaged white matter ber integrity compared to healthy controls. Additionally, damage to several brain regions was associated with cognitive impairment 3,4 . Lei et al 5 found that the network topology in MMD was signi cantly reorganized based on resting-state functional MRI.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the disease has been associated with damage to the frontal and temporal lobes, which play key roles in speech production and comprehension (Hu et al, 2022;Saito et al, 2021). The study by Zuo and colleagues showed that nearly 30% of patients (in a sample of 142 individuals) with moyamoya disease had speech impairments in the form of dysarthria and aphasia (Zuo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%